Analysis of the Cx32, MPZ and PMP22 mutations in the Turkish Charcot-Marie-Tooth patients - Maracı, Nazmiye Öncü. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Charcot-Marie-Tooth disease is the most common hereditary peripheral neuropathy with a prevalence rate of one in 2500. Although the disease is classified as demyelinating and axonal CMT based on clinical investigations, genetic studies revealed more than 28 genes and subtypes for both axonal and demyelinating forms. In a total of 161 unrelated CMT patients were analyzed in this study. The incidence of CMT1A duplication in the Turkish population was found to be significantly lower (41.6 per cent) compared to that of other populations (70 per cent). The frequency of the HNPP deletion was found to be 66.6 per cent. Although this rate is lower than that of other populations (86 per cent), the difference was not statistically significant. In this study, five nucleotide variations were identified; a novel and a previously reported mutation in Cx32, a previously reported polymorphism in MPZ and two novel mutations in PMP22. Phenotype/genotype correlations were performed for the identified mutations and the observed phenotype of the patients was found to be compatible with the mutations they carry. Identification of causative mutations in the patients verifies the clinical diagnosis and leads the clinicians for choosing the therapeutic approach. However, for the patients that could not be genetically diagnosed further research is required to identify the pathogenic mutations in other CMT genes. On the other hand, identification of further mutations and genotype/phenotype correlations are of critical importance and will help elucidation of the pathogenic mechanisms leading to the CMT disease.
Keywords: Charcot-Marie-Tooth disease.; Genetic disorders.